Inhibitory Effects of β-caryophyllene on Helicobacter pylori Infection: A Randomized Double-blind, Placebo-controlled Study - Hyun Ik Shim; Dong Jin Song; Cheol Min Shin; Hyuk Yoon; Young Soo Park; Nayoung Kim; Dong Ho Lee (The Korean Journal of Gastroenterology, 2019)
Background/Aims: Helicobacter pylori (H. pylori) infections, which cause a variety of gastrointestinal symptoms, are common in South Korea. Recent reports have shown a decline in the H. pylori eradication rates. β-caryophyllene is a natural bicyclic sesquiterpene that occurs in a wide range of plant species, such as cloves, basil, and cinnamon. β-caryophyllene has been reported to have anti-inflammatory and anti-bacterial effects. This study investigated the inhibitory effects of β-caryophyllene on H. pylori and its potential role as an alternative gastrointestinal drug. Methods: This 8-week, randomized double-blind, placebo-controlled trial categorized subjects into a β-caryophyllene group (33 patients who received 126 mg/day of β-caryophyllene) and a placebo group (33 patients who received a placebo preparation). The inflammation level of H. pylori infiltration and the eradication rates were evaluated endoscopically and with the urea breath test (UBT) in both groups before and after administering the medication. The serum cytokine levels (tumor necrosis factor-α, and interleukin [IL]-1β and IL-6) were compared in both groups before and after administering the medication. Results: Complete eradication was not observed in either group. Moreover, there was no significant change in the UBT and updated Sydney score. On the other hand, the β-caryophyllene group showed significant improvement in nausea (p=0.025) and epigastric pain (p=0.018), as well as a decrease in the serum IL-1β levels (p=0.038). Conclusions: β-caryophyllene improves dyspepsia symptoms and can be considered a useful supplementary treatment for gastrointestinal disease.